n-tupled Common Fixed Point Theorems via alpha-series in Ordered Metric Spaces (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to establish some results about the existence and uniqueness of $n$-tupled fixed point that extends the previous results, using the concept of an $α$-series for sequence of mappings having mixed monotone property in the framework of ordered complete metric spaces.Â  The main result is supported with the aid of an illustrative example.
Keywords: $α$-series; Compatible mappings; Common fixed point; Ordered metric space